Evaluation of SMAN Olahraga and PPLP Development in Lampung - Sumantri, Riyan Jaya; Demirci, Nevzat; Widiyono, Ibnu Prasetyo; Cahyo, Anggoro Dwi (JUMORA: Jurnal Moderasi Olahraga, 2023)
The Lampung State High School (SMAN) Olahraga and Student Education and Training Center (PPLP) recruits and develops talented Olahraga students to achieve high achievements at the national and even international levels. This research aims to analyze the context, input, process and product of SMAN Olahraga and PPLP Lampung students. Evaluation research with quantitative descriptive methods using the CIPP model design. The population of this study were 20 SMAN Olahraga students and 20 PPLP students from various high-achieving schools in Lampung. The sampling technique used a total sampling of 20 SMAN Olahraga students and 20 PPLP Lampung students. Data collection techniques use questionnaires, in-depth interviews and documentation. The results of the research show that 1) the development context of SMAN Olahraga and PPLP has a match between the vision and mission and the goals to be achieved, 2) the planning input for SMAN Olahraga and PPLP Lampung is equipped with the availability of training planning documents and training program guidelines, 3) The supervision process is carried out as a means to evaluate the implementation of SMAN Olahraga and PPLPLampung, 4) The SMAN Olahraga and PPLP Product Programs are able to improve the quality of athletes. The results of the research are useful as recommendations for SMAN Olahraga, PPLP, Education & Culture Service and Youth and Olahraga Service in Lampung to focus more on developing coaching and training programs.Keywords: Sports Development Lampung, SMAN Olahraga, PPLP Lampung